SAT0023 Control of cytokine mrna degradation by the histone deacetylase inhibitor itf2357 in rheumatoid arthritis fibroblast-like synoviocytes. (12th June 2018) - Angiolilli, C.; Kabala, P.; Grabiec, A.; Rossato, M.; Lai, W.; Blackshear, P.; Reedquist, K.; Baeten, D.; Radstake, T.
Abstract : Background: Control of cytokine mRNA degradation acts as an essential check-point to limit the overproduction of inflammatory proteins. 1 In rheumatoid arthritis (RA), altered expression of the mRNA-degrading protein TTP (tristetraprolin, ZFP36 ) has been recently reported in synovial tissue, possibly contributing to the perpetuating inflammatory loop in the synovium. 2 Histone deacetylase inhibitors (HDACi) are small molecule drugs suppressing cytokine production in vitro and in vivo and displaying initial safety and efficacy in the treatment of systemic onset juvenile idiopathic arthritis. 3, 4 However, their transcriptional and post-transcriptional mechanisms of action are not yet completely characterised. Objectives: We aimed to investigate the mRNA degrading properties of the HDACi ITF2357 on a panel of inflammatory mediators in RA fibroblast-like synoviocytes (FLS). Methods: The effects of ITF2357 on the expression and mRNA stability of IL-1β-inducible genes in FLS were analysed using array-based qPCRs and Luminex. The expression of primary and mature cytokines transcripts, the mRNA levels of TTP and other AU-rich element binding proteins (ARE-BP) and the cytokine profile of fibroblasts derived from ZFP36 +/+ and ZFP36 -/- mice was measured by qPCR. ARE-BP silencing was performed by siRNA-mediated knockdown, and TTP post-translational modifications analysed by immunoblotting. Results: ITF2357 reduced the expression of 85% of the analysed IL-1β-inducible transcripts, including cytokines ( IL6, IL8 ), chemokines ( CXCL2, CXCL5, CXCL6, CXCL10 ), matrix-degrading enzymes ( MMP1, ADAMTS1 ) and other inflammatory mediators. Analyses of mRNA stability demonstrated that ITF2357 accelerates IL6, IL8, PTGS2, and CXCL2 mRNA degradation, a phenomenon associated with the enhanced transcription of TTP, but not other ARE-BP, and the altered post-translational status of TTP protein. TTP knockdown potentiated cytokine production in RA FLS and murine fibroblasts. Conclusions: Our study identifies that regulation of cytokine mRNA stability is a predominant mechanism underlying ITF2357 anti-inflammatory properties, occurring via regulation of TTP. These results highlight the therapeutic potential of ITF2357 in the treatment of RA. References: [1] Turner M, Diaz-Munoz MD. RNA-binding proteins control gene expression and cell fate in the immune system. Nat Immunol2018. [2] Ross EA, Naylor AJ, O'Neil JD, et al. Treatment of inflammatory arthritis via targeting of tristetraprolin, a master regulator of pro-inflammatory gene expression. Ann Rheum Dis2016. [3] Joosten LA, Leoni F, Meghji S, Mascagni P. Inhibition of HDAC activity by ITF2357 ameliorates joint inflammation and prevents cartilage and bone destruction in experimental arthritis. Mol Med2011. [4] Vojinovic J, Damjanov N, D'Urzo C, et al. Safety and efficacy of an oral histone deacetylase inhibitor in systemic-onset juvenile idiopathic arthritis. Arthritis Rheum2011. Disclosure of Interest: None declared